Human Resource Flexibility and Organizational Performance in Insurance Industry - Mir Ali Seyed Naghavi; Mahdi Haghighi Kaffash; Vahid Najafi Kalyani (مطالعات مدیریت بهبود و تحول, 2012)
Human resource flexibility has become an undeniable imperative in the uncertainty and dynamic environment of today since it gives organization the appropriate response to the fast environmental changes. While researchers in strategic human resource management consider human resource flexibility as a source of sustainable competitive advantage for the firms, the process through which human resource flexibility have been affected organizational performance has not been empirically investigated. Based on the study of 123 organizational units in 17 insurance companies operating in Iran, this paper tries to clarify the content of the causal relationship between human resource flexibility and organizational performance by extending and testing the causal model. Evidence indicates that HR flexibility has a positive effect on the organizational performance in insurance companies. Results of structural equation modeling of the causal model indicate that all the path’s coefficients are significant, so all the research hypotheses are supported. The research findings suggest that, between the dimensions of HR flexibility, skill flexibility has the greatest effect on the organizational performance. Therefore, employee skills and their ability to acquire new skills, play an important role in competitive advantage and performance in insurance companies.